Status dan Hak Anak Tak Sah Islam dalam Undang-Undang di Malaysia (Sains Humanika, 2018)
Illegitimate child refers to a child conceived during sexual intercourse outside of wedlock. The jurists have different views regarding the gestation period of pregnancy that affects the legitimacy status of the child. The objective of this article is to analyze the different views of the jurists regarding the status as well as rights of the illegitimate child in Islam and current religious ruling implemented in Malaysia. This article also analyzes the rights of the illegitimate child towards a personal identity that involved lineage that effects on how his/her name and surname will be stated on birth certificate according to the Islamic and civil law in Malaysia. Issues on custody, maintenance, marriage guardianship of the illegitimate child and his/her relation with biological father that married to his / her mother will also be discussed according to the opinions of the jurists as well as Islamic family law in Malaysia. This study utilized content analysis method on discussions put forward by the jurists in authoritative jurisprudence books as well as contemporary jurisprudence books and law provisions that are provided in Islamic and civil law implemented in Malaysia to date. The findings show that Islamic family law protects rights of the illegitimate child in terms of self-identity (lineage), custody, maintenance and marriage guardianship. However, the issue regarding the surname of the illegitimate child was raised in Civil Court, arguing that he/she should be allowed to be named to his/her biological father who had married the mother. This issue needs to be scrutinized. The amendment should be carried out so that matters related to the Muslims' personal laws are implemented according to the Islamic law.
Keywords: Child; illegitimate child; rights of the illegitimate child; islamic law; civil law